2015
DOI: 10.18632/oncotarget.3121
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the in vivo half-life of endostatin and its improved anti-tumor activities upon fusion to a humanized antibody against tumor-associated glycoprotein 72 in a mouse model of human colorectal carcinoma

Abstract: Endostatin is an endogenous angiogenesis inhibitor that exhibits potential anti-tumor efficacy in various preclinical animal models. However, its relatively short in vivo half-life and the long-term, frequent administration of high doses limit its widespread clinical use. In this study, we evaluated whether a fusion protein of murine endostatin (mEndo) to a humanized antibody against tumor-associated glycoprotein 72 (TAG-72), which is highly expressed in several human tumor tissues including colon cancer, can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Endostatin has been fused to the proapoptotic domain (BH3) of the BAX protein (Chura-Chambi et al, 2014 ), to tumor necrosis factor-related apoptosis-inducing ligand (Zheng et al, 2013 ) and one of its anti-angiogenic sequences to an heptapeptide inhibitor of MMPs (Qiu et al, 2013 ). Endostatin has also been fused to protein sequences targeting it to tumors and/or tumor vasculature such as humanized antibodies against tyrosine kinase-type receptor HER2 (Shin et al, 2011 ) or against tumor-associated glycoprotein 72 highly expressed in human tumor tissues (Lee et al, 2015 ), the RGD integrin-binding sequence (Jing et al, 2011 ), and a liver-targeting peptide (circumsporozoite protein CSP I-plus (Ma et al, 2014 ; Bao et al, 2015 ).…”
Section: Matricryptins As Potential Drugsmentioning
confidence: 99%
“…Endostatin has been fused to the proapoptotic domain (BH3) of the BAX protein (Chura-Chambi et al, 2014 ), to tumor necrosis factor-related apoptosis-inducing ligand (Zheng et al, 2013 ) and one of its anti-angiogenic sequences to an heptapeptide inhibitor of MMPs (Qiu et al, 2013 ). Endostatin has also been fused to protein sequences targeting it to tumors and/or tumor vasculature such as humanized antibodies against tyrosine kinase-type receptor HER2 (Shin et al, 2011 ) or against tumor-associated glycoprotein 72 highly expressed in human tumor tissues (Lee et al, 2015 ), the RGD integrin-binding sequence (Jing et al, 2011 ), and a liver-targeting peptide (circumsporozoite protein CSP I-plus (Ma et al, 2014 ; Bao et al, 2015 ).…”
Section: Matricryptins As Potential Drugsmentioning
confidence: 99%
“…Furthermore, ES suppressed the expression of VEGF, matrix metalloproteinases, fibroblast growth factor and cell adhesion molecule ( 37 , 38 ). Certain previous studies revealed that tumor growth was inhibited in transgenic mice overproducing ES ( 39 , 40 ). Based on the results of the present study, the upregulation of ES and downregulation of VEGF and OPN may be responsible for the anticancer effect of Delisheng on Hep3B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these studies fall under a large blanket of experimental findings that show RE’s effect on the vascular endothelium and successfully served as a validation of the original work by O’Reilly and colleagues [ 38 ]. Importantly, anti-angiogenic drugs like RE target rapidly proliferating tumour-associated endothelial cells rather than relatively dormant endothelial cells in healthy tissue, making them less toxic than chemotherapeutic agents [ 82 ].…”
Section: Endostatin and Its Mechanism Of Actionmentioning
confidence: 99%